أثر الذكاء الاستراتيجي على أداء العاملين في شركات الاتصالات الأردنية - المومني, ياسر عيسى; المومني, لبنى مصطفى (جامعة الوادي - University of Eloued, 2023)
The study aimed to figure out the impact of the strategic intelligence on the performance of the employees in the Jordanian telecommunications companies through the dimensions of the strategic intelligence (foresight, system thinking, and partnership) and their impact on the performance of employees. The study adopted the descriptive, analytical approach as well as the questionnaire as a tool for data collection. (75) questionnaires were distributed to the members of the study sample, and they were analyzed through the (SPSS). The study concluded that the level of applying the strategic intelligence dimensions in the telecommunications companies was high where the foresight dimension ranked first followed by the partnership dimension in the second place and the dimension of the system thinking in the third and final dimension. The results also showed that the level of the performance of the employees in the Jordanian telecommunications companies was medium, and a statistically significant impact at sig. (α≤0.05) for the dimensions of the strategic intelligence on the performance of the employees in the telecommunications companies. The study recommends the need to adopt and deepen the concept of the strategic intelligence among the departments of organizations due to its great importance in facing changes and developments in the surrounding environment to help them make the right decisions in addition to pay attention to training the employees and adopt their new and creative ideas in line with the current and future situation.
The impact of strategic intelligence on the performance of employees in Jordanian telecommunications companies
مقال
Keywords: الذكاء الاستراتيجي ; أداء العاملين ; شركات الاتصالات الأردنية; strategic intelligence, the performance of employees, Jordanian telecommunications companies.